2001
DOI: 10.1142/s0192415x01000502
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SKI 306X, a New Herbal Anti-Arthritic Agent, in Patients with Osteoarthritis of the Knee: A Double-Blind Placebo Controlled Study

Abstract: SKI 306X is a purified extract from a mixture of three oriental herbal medicines (Clematis mandshurica, Trichosanthes kirilowii and Prunella vulgaris) that have been widely used for the treatment of inflammatory diseases such as lymphadenitis and arthritis in far East Asia. A double-blind, controlled study was performed to evaluate the efficacy and safety of SKI 306X with placebo in 96 patients with classical osteoarthritis of the knee. Patients were randomized to four treatment groups: placebo, 200 mg, 400 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 7 publications
0
51
0
2
Order By: Relevance
“…In previous studies, we reported the protective effects of SKI306X on rabbit articular cartilage and compared it with other OA drugs using in vivo models (9). A double blind and placebo-controlled study also confirmed the clinical efficacy and good tolerability of SKI306X in patients with OA in the knee (10). In another clinical study, this herbal extract was well tolerated by patients and demonstrated to have clinical efficacy comparable to that of diclofenac SR (slow released) (11).…”
Section: Introductionmentioning
confidence: 62%
“…In previous studies, we reported the protective effects of SKI306X on rabbit articular cartilage and compared it with other OA drugs using in vivo models (9). A double blind and placebo-controlled study also confirmed the clinical efficacy and good tolerability of SKI306X in patients with OA in the knee (10). In another clinical study, this herbal extract was well tolerated by patients and demonstrated to have clinical efficacy comparable to that of diclofenac SR (slow released) (11).…”
Section: Introductionmentioning
confidence: 62%
“…Recent clinical trial suggested that extracted mixture of Clematis exerted protective effects on OA 13. However, the precise mechanism and responsible molecules for this effect are not obvious presently.…”
Section: Introductionmentioning
confidence: 99%
“…SKI306X had been reported to have protective effects in articular cartilage. 5) The double blind, placebo-controlled study also confirmed the clinical efficacy and good tolerability of SKI306X in patients with OA in the knee 6) and in another clinical study, this herbal extract was well tolerated and demonstrated clinical efficacy comparable to that of diclofenac SR (slow released). Another clinical study is underway to determine the efficacy of SKI306X in RA patients.…”
mentioning
confidence: 66%